An early regulatory mechanism of hyperinflammation by restricting monocyte contribution - Akiyama, Megumi; Kanayama, Masashi; Umezawa, Yoshihiro; Nagao, Toshikage; Izumi, Yuta; Yamamoto, Masahide; Ohteki, Toshiaki (Frontiers in Immunology, 2024)
Innate immune cells play a key role in inflammation as a source of pro-inflammatory cytokines. However, it remains unclear how innate immunity-mediated inflammation is fine-tuned to minimize tissue damage and assure the host's survival at the early phase of systemic inflammation. The results of this study with mouse models demonstrate that the supply of monocytes is restricted depending on the magnitude of inflammation. During the acute phase of severe inflammation, monocytes, but not neutrophils, were substantially reduced by apoptosis and the remaining monocytes were dysfunctional in the bone marrow. Monocyte-specific ablation of Casp3/7 prevented monocyte apoptosis but promoted monocyte necrosis in the bone marrow, leading to elevated levels of proinflammatory cytokines and the increased mortality of mice during systemic inflammation. Importantly, the limitation of monocyte supply was dependent on pro-inflammatory cytokines in vivo. Consistently, a reduction of monocytes was observed in the peripheral blood during cytokine-release syndrome (CRS) patients, a pathogen-unrelated systemic inflammation induced by chimeric antigen receptor-T cell (CAR-T cell) therapy. Thus, monocytes act as a safety valve to alleviate tissue damage caused by inflammation and ensure host survival, which may be responsible for a primitive immunecontrol mechanism that does not require intervention by acquired immunity.